Public Education Under Siege - Michael B. Katz, Mike Rose (University of Pennsylvania Press, 2013)
In his remarks at the Centennial Conference of the National Urban League on July 29, 2009, President Barack Obama reminded his audience that â€œfrom day one of this administration, weâ€™ve made excellence in American educationâ€”excellence for all our studentsâ€”a top priority.â€ Even Republicans would not have disagreed with this choice. The imperative of educational reform became a national rallying cry issued from the left and right as politicians on both sides of the aisle claimed that a slide in the quality of American public education left the nation behind its competitors, its future prosperity imperiled. Obama backed up his clarion call with his $4 billion Race to the Top Fund and billions more for education embedded in the American Recovery and Reinvestment Act (also referred to as the economic stimulus bill). As educational reform blossomed around the country, a rough consensus emerged about the source of the problem and the direction that change should take. Blame fell heavily on teachers and especially on their unions, which, it was claimed, blocked reform by putting their own self-interest ahead of the well-being of their students. Blame extended backward to the schools of education that had trained legions of ineffective teachers, the lack of rigor that permitted â€œsocial promotion,â€ unreliable methods for assessing student progress and teacher quality, and job tenure which protected bad teachersâ€”deficiencies all summed up with the term accountability. Accountability required improved methods of assessment and the injection of competition into a moribund system. Reform, in short, rested on new high-stakes testing regimes and the application of market principles to public education.